Foreign Banks’ Presence and Domestic Bank Performance: Evidence from Indonesia - Aina Mardiya; Irwan Trinugroho (Faculty of Economic and Business, 2018)
We examine the impact of foreign presence on domestic banks’ performance by studying conventional commercial banks in Indonesia. We use monthly financial information of 97 commercial banks from 2003 through 2013 resulting in 8,600 observations. We use a panel data regression (Panel Least Square method) to test our hypotheses. Our results show that overall, foreign presence decreases the performance of domestic banks. Going deeper, we find that foreign presence reduces state-owned banks’ profitability as well as private domestic banks’ profitability. However, there is no significant effect of foreign presence on the performance of regional development banks. Little evidence found on the effect of foreign presence on overhead cost.DOI:10.15408/etk.v17i2.7769